Library Hosted Open Access Journals as Tools for Teaching Publishing Practices - Roinila, Markku; Ala-Kyyny, Juuso (Journal of EAHIL, 2022)
We will discuss teaching publishing practices and different forms of student participation in three open access journals hosted by Helsinki University Library’s Editori-service, two of which are from a field of neurosciences. As a theoretical framework, we will distinguish between classroom journals (with students providing the content and teacher acting as an editor), student-led journals (students acting in both roles) and mock journals (which are like classroom journals, but the journal remains unpublished). Our discussion is founded on interviews of journal editors and analysis of student roles in the journals. In addition, we will mention one previous experiment of a mock journal in Editori-service, related to a Doctoral School working seminar in Humanities and Social Sciences.